2020
DOI: 10.7759/cureus.7957
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Hypertension Among Children Attending Out Patient Department of a Tertiary Care Hospital in Karachi

Abstract: Introduction: The childhood obesity epidemic has caused the global prevalence of hypertension (HTN) in children to increase from 2% to 4%. However, there is limited data regarding this issue in Pakistan. Hence this cross-sectional study aims to document the prevalence of HTN and its risk factors among children visiting the out patient department (OPD) of a government hospital in Karachi, which is one of the largest cities in Pakistan. Methods: One thousand children aged between 4 and 12 years who visited the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
3
12
1
Order By: Relevance
“…Bilal et al, conducted a similar study in Karachi in 2019 in which hypertensive prevalence was 21.1% among males and 19.3% among female children, although this gender difference was not statistically significant considering hypertension prevalence. 16 Similar pattern was found in Zhai et al, study from China, where 20.2% of the male population and 16.3% of the female population were hypertensive. 17 Male gender and baseline masked hypertension were independent risk factors for developing sustained hypertension in preadolescents and adolescents.…”
Section: Discussionsupporting
confidence: 80%
“…Bilal et al, conducted a similar study in Karachi in 2019 in which hypertensive prevalence was 21.1% among males and 19.3% among female children, although this gender difference was not statistically significant considering hypertension prevalence. 16 Similar pattern was found in Zhai et al, study from China, where 20.2% of the male population and 16.3% of the female population were hypertensive. 17 Male gender and baseline masked hypertension were independent risk factors for developing sustained hypertension in preadolescents and adolescents.…”
Section: Discussionsupporting
confidence: 80%
“…13 These findings were also supported by a study conducted in Karachi that showed a similar relation in children. 14 Indian study conducted at Amritsar also reported similar findings. 15 Significant IAD difference was observed in systolic and diastolic blood pressure of obese and nonobese subjects.…”
Section: Discussionsupporting
confidence: 63%
“…However, the point of concern is exactly how much alteration in blood pressure is existent. 14 Our study comprised 100 subjects, among them 46% were obese, and 54% were non-obese. Similar results were also found in a study done by Khan et al, who found 37% of the participants obese.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence in our unexposed group is similar to previous BP report in ''healthy'' Pakistani children. 23,24 A recent meta-analysis indicated that reductions in BP as small as 10 mm Hg in adults can cause a 20% reduction in stroke and 17% reduction in coronary artery disease, thus indicating the importance of early screening and aggressive management for an impact on CVD morbidity and mortality. 25 On subgroup analysis, children in the early-onset PE subgroup had a higher frequency of stage 1 HTN compared with healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%